HUMAN-GEOGRPAHICAL FEATURES OF THE POPULATION REPRODUCTION IN CHUGUIV DISTRICT OF KHARKIV REGION - Кандиба, Юрій; Логвинова, Марина (Human Geography Journal, 2016)
The article deals with dynamic, modern trends of the main demographical processes in Chuguiv district of Kharkiv region. Changes causes of birthrate, mortality rate, natural growth, migration processes were characterized.  Regionalization of the demographic situation indicators within the settlements of Chuguiv district was conducted, their territorial differentiation was analyzed. Measures on demographic situation improvement in Chuguiv district were proposed based on the received results.